Pengaruh Sikap Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Kinanty Patopang - ., A. Dirwan (Jurnal Manajemen, 2014)
The  purpose  of this study was to determine the  influence  of work  attitude and motivation  on employees  pefonnance  at PT Kinanty  Patopang.  The subject of this research  were  50  employees.  By using 5  Likert Scale.  The frame work of this research was  based   on  that  work  attitude  (X1)   and  work  motivation   (X2)   had  influence  of employees  performance  (Y). The work attitude  was  measured  bay 30  items  question, work motivation  was measured  bay 31 items question, and employees  performance was measured  with 39 items question/statement.   Data analysis  used  in this research was a multiple  regression   to  analyzed  data.  Obtained  data  then  were  examined  with  SPSS17.0 version.  From the research  it can concluded  that:  (I) there  was influence of work attitude  toward  employees  performance; (2)   there  was  influence of work  motivation toward    employees   performance, (3)  there  was  influence of work  attitude  and  work motivation  simultaneously toward  employees  performance of  PT.  Kinanty Patopang.